THE RETURN OF NEO-PROTECTIONISM? - Malte Pehl LL.M. (Consilium LLC, 2021)
As a moral corrective, compliance rules may be particularly important for the internal relationships of employees in a company and for the relationships between different companies. There original purpose was to ensure correctness and fairness in day-to-day business.